INDEPENDENSI DAN KUALITAS AUDITOR INTERNAL TERHADAP TEMUAN AUDIT - TRIYANTI SUBIYANTO, NOVA (Berkala Ilmiah Mahasiswa Akuntansi)
The role of internal auditor is an independent appraisal function, which exists in an organization and has the objective to test and evaluate the activities of organizations that implemented. With the internal auditor, you will get the results of the audit process is in the form of audit findings. Internal Auditor is involved in an independent appraisal function within an organization. The independence is a policy which provides that a public accounting firm reasonable assurance that the auditors, at all levels or tiers, to maintain independence in accordance with the ditetapkam Public Accountants Professional Standards (SPAP). Internal auditors should have independence in conducting audits and express their views and thoughts in accordance with applicable auditing standards. The independence is very important, in order to have optimal benefits for all stakeholders. To improve the quality of auditors role in revealing the findings of the audit, internal auditors need the professional skills: the ability of individuals in performing tasks, which means qualified personnel in accordance with its internal auditor duties.